2020
DOI: 10.3389/fnins.2020.00776
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk Between Ferroptosis and Cerebral Ischemia

Abstract: Recently, ferroptosis has been revealed as a new form of regulated cell death. Distinct from apoptosis and necrosis, ferroptosis is evoked by iron-dependent lipid peroxidation. Furthermore, the metabolism of iron, lipids, and amino acids plays a significant regulatory role in ferroptosis, which can be reversed by glutathione peroxidase 4 and ferroptosis suppressor protein 1. Ferroptosis is implicated in the onset and development of numerous neurological diseases. Emerging studies have reported that ferroptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 76 publications
(121 reference statements)
0
37
0
Order By: Relevance
“…Necroptosis, an alternative form of programmed necrosis, is regulated by receptor-interacting protein (RIP) 1 activation and by RIP3 and mixed-lineage kinase domain-like (MLKL) phosphorylation via inhibition of caspase-8. Emerging studies have reported that ferroptosis and necroptosis both induce and aggravate brain tissue damage following the onset and development of cerebral ischemia and cerebral ischemia/reperfusion injury (CIRI) [4][5][6][7][8]. Regarding therapy, tissue plasminogen activator (t-PA), the only thrombolytic drug approved by the Food and Drug Administration for ischemic stroke treatment, dissolves blood clots by activating a proteolytic enzyme [8].…”
Section: Introductionmentioning
confidence: 99%
“…Necroptosis, an alternative form of programmed necrosis, is regulated by receptor-interacting protein (RIP) 1 activation and by RIP3 and mixed-lineage kinase domain-like (MLKL) phosphorylation via inhibition of caspase-8. Emerging studies have reported that ferroptosis and necroptosis both induce and aggravate brain tissue damage following the onset and development of cerebral ischemia and cerebral ischemia/reperfusion injury (CIRI) [4][5][6][7][8]. Regarding therapy, tissue plasminogen activator (t-PA), the only thrombolytic drug approved by the Food and Drug Administration for ischemic stroke treatment, dissolves blood clots by activating a proteolytic enzyme [8].…”
Section: Introductionmentioning
confidence: 99%
“…That's why not all cells are susceptible to the same extend. The ferroptosis is reported as one of the fundamental forms of cell death in many neurological diseases [103], including Alzheimer's disease or Parkinson's disease [104], and Cerebral Ischemia [105]. The susceptibility of neural cells to ferroptosis, we explain the following way in the context of our research.…”
Section: Lipid Oxidation and Pore Formation Beyond Electroporationmentioning
confidence: 93%
“…In neurology, ferroptosis has been confirmed to participate in intracerebral hemorrhage, subarachnoid hemorrhage, Alzheimer’s disease, amyotrophic lateral sclerosis, and Parkinson’s disease [ 14 – 18 ]. Preliminary evidence reveals that ferroptosis deteriorates ischemia-induced brain damage, while the administration of ferrostatin-1 (an inhibitor of ferroptosis) can effectively reverse induced damage [ 19 , 20 ]. Recently, increasing studies have focused on finding biomarkers of ferroptosis in multiple levels, including morphology, biochemistry, protein, and gene [ 21 ].…”
Section: Introductionmentioning
confidence: 99%